Human brain networks: an investigation on cortical thickness resting-state fMRI and structural connectivity as assessed by tractography - Figueira, Ana Filipa Canha (2014)
Tese de mestrado integrado em Engenharia Biomédica e Biofísica, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2013